Continuous Glucose Monitoring as a Valuable Tool in the Early Detection of Diabetes Related to Cystic Fibrosis - Gojsina, Bojana; Minic, Predrag; Todorovic, Sladjana; Soldatovic, Ivan; Sovtic, Aleksandar (Frontiers in Pediatrics, 2021)
Aims: We evaluated the impact of cystic fibrosis-related diabetes (CFRD) on lung disease and nutritional status. Study Design: The retrospective cohort study evaluated the subjects' medical records from 2004 to 2019. All participants older than 10 years diagnosed by a 30-minutely sampled OGTT formed OGTT-CFRD subgroup. The participants diagnosed with continuous glucose monitoring (CGM) (at least two peaks above 11.1 mmol/l and more than 10% of recorded time above 7.8 mmol/l) formed a CFRD-CGM subgroup. The participants without CFRD formed a non-CFRD group. The longitudinal follow-up was made 2 years before and 3 years after insulin therapy initiation. Results: Of 144 participants included, aged 10–55 years (44% males), 28 (19.4%) had CFRD. The HbA1c was significantly lower in the CGM-CFRD in comparison to the OGTT-CFRD subgroup (5.9 ± 0.62 and 7.3 ± 1.7% respectfully; p = 0.04). Subjects with CFRD were malnourished in comparison to non-CFRD, with significant improvements with insulin replacement therapy in regard to BMI Z-score (−1.4 ± 1.3 vs. −0.5 ± 1.2%, p = 0.04) and pulmonary exacerbation score (p = 0.02). In OGTT-CFRD subgroup there is an increase in FEV1 (62.7 ± 26.3 to 65.1 ± 21.7%, p = 0.7) and decrease in FVC (from 76.4 ± 24.2 to 71.2 ± 20%, p = 0.003) from diagnosis to second year of follow-up. In CGM-CFRD subgroup there was a decrease in FEV1 (from 58.2 ± 28.2 to 52.8 ± 25.9%, p = 0.2) and FVC-values (from 72.4 ± 26.5 to 67.4 ± 29.1%, p = 0.08).Chronic Pseudomonas aeruginosa infection was more prevalent in the CFRD group (p = 0.003). Conclusion: Continuous glucose monitoring is a useful tool for insight of glucose impairment and diagnosis of CFRD. Early recognition of CFRD and therapeutic intervention has favorable effects on clinical course of the disease.